Dissecting genomic regions and candidate genes for pod borer resistance and component traits in pigeonpea minicore collection - Moghiya, Abhinav; Munghate, R.S.; Sharma, Vinay; Mishra, Suraj Prashad; Jagdish, Jaba; Gaurav, Shailendra Singh; Gangurde, Sunil S.; Dube, Namita; Rangari, Sagar Krushnaji; Roychowdhury, Rajib; Gangashetty, Prakash; Sharma, Hari Chand; et al. (Frontiers Media, 2025)
Background: Pigeonpea is an important leguminous food crop primarily grown in tropical and subtropical regions of the world and is a rich source of high-quality protein. Biotic (weed, disease, and insect pests) and abiotic stresses have significantly reduced the production and productivity of pigeonpea. Helicoverpa armigera, also known as the pod borer, is a major pest in pigeonpea. A substantial investigation is needed to comprehend the genetic and genomic underpinnings of resistance to H. armigera. Genetic improvement by genomics-assisted breeding (GAB) is an effective approach for developing high-yielding H. armigera-resistant cultivars. Still, no genetic markers and genes linked to this key trait have been detected in pigeonpea. In this context, a set of 146 pigeonpea minicore accessions were evaluated for four H. armigera-resistant component traits, namely, pod borer resistance (PBR), days to 50% flowering (DF), days to maturity (DM), and grain yield (GY), for three consecutive seasons under field conditions.